Uniform Crime Reports: Arrest Data for the 75 Most Populous Counties in the United States, 1986 ([Verlag nicht ermittelbar], 1989)
The files in this collection contain counts of arrests and offenses for Part I, Index Offenses, and Part II, Other Offenses: murder, rape, robbery, assault, burglary, larceny, auto theft, arson, forgery, fraud, embezzlement, vandalism, weapons violations, sex offenses, drug and alcohol abuse violations, gambling, vagrancy, curfew, and runaways. County populations are also reported.